Dormancy-Associated Gene 1 (OsDRM1) as an axillary bud dormancy marker Retarding Plant Development, and Modulating Auxin Response in Rice (Oryza sativa L.) - Chen, Ruihong (Journal of plant physiology, 2023)
Copyright © 2023 Elsevier GmbH. All rights reserved.